Energy system contributions and determinants of performance in 400-meter military obstacle course - DALEI WANG; GUOLE JIANG; SHUANG QIN; DEYU SUN; JIEXING YAN; YUNJI CHEN; YEQIONG WANG; YIJIE TAN (Anais da Academia Brasileira de Ciências)
Abstract The purpose of the study is to explore the energy system contributions and determinants of performance in 400-meter military obstacle course (400m-MOC), and establish a model for predicting the performance in 400m-MOC. 50 male cadets participated in this study. Using portable gas analyzers and a blood lactate test, the energy system contributions were calculated during 400m-MOC test. Correlation analysis was conducted to ascertain the relationships between the performance of the 400m-MOC and the contributions of three different energy systems, as well as body morphology and various physical fitness components. A linear regression model was developed to predict the performance outcomes in 400m-MOC. The contributions of three different energy systems during 400m-MOC test were: phosphagen system (17.94±1.23%), glycolytic system (27.94±2.48%), and aerobic oxidative system (54.12±2.76%). Completion time for the 400m-MOC test correlates significantly with military service length, strength, BMI, speed, speed endurance, and aerobic endurance capability. The regression equation was formulated as: estimated 400m-MOC completion time=22.556 + 0.065 × 5000-meter running time-52.677 × (pull-up reps/body weight) + 0.582 × 400-meter running time. The 400m-MOC is primarily powered by the aerobic oxidative system, with aerobic endurance, upper body strength, and speed endurance being particularly crucial factors affecting its performance.